CHANGES IN THE ENVIRONMENTAL FEATURES OF PULICAT LAKE IN RELATION TO TIDES - Kaliyamurthy, M (Indian Journal of Fisheries, 2011)
The present observations were undertaken to gain knowledge on the range of variations in some of the important hydrobiological parameters in relation to tidal rhythm, as a part of the investigation on the ecology of the Pulicat lake. Information available on the tidal cycles in some of the Indian estuaries is mainly due to the works of Rangarajan (1958), George and Kartha (1963), Qasim and Gopinathan (1969), Dehadrai (1970b), Sarma and Ganapati (1970) and Dehadrai and Bhargava (1972). But nothing is known about this important aspect of the ecology of the Pulicat lake.